2014
DOI: 10.1007/s10482-014-0142-3
|View full text |Cite
|
Sign up to set email alerts
|

Halocynthiibacter namhaensis gen. nov., sp. nov., a novel alphaproteobacterium isolated from sea squirt Halocynthia roretzi

Abstract: A Gram-negative, non-motile and rod-shaped bacterial strain, designated RA2-3(T), was isolated from a sea squirt (Halocynthia roretzi) collected from the South Sea, Korea, and its taxonomic position was investigated by using a polyphasic approach. Strain RA2-3(T) was observed to grow optimally at 25 °C, at pH 7.0-7.5 and in the presence of 2 % (w/v) NaCl. Strain RA2-3(T) exhibited the highest 16S rRNA gene sequence similarity values to the type strains of Litoreibacter meonggei (95.7 %), Planktotalea frisia (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…The fatty acid profile of strain BS-W9 T was distinguished from that of the type strain of H. namhaensis by differences in the presence and proportions of some fatty acids, particularly cyclo C 19 : 0 ω8 c and 11-methyl C 18 : 1 ω7 c (). The fatty acid profile of strain BS-W9 T could also be distinguished from those of some phylogenetically related taxa, Pseudopelagicola gijangensis , Pelagicola litoralis and Ascidiaceihabitans donghaensis , particularly by the presence of cyclo C 19 : 0 ω8 c (; Kim et al , 2014a, b, c). The major polar lipids detected in strain BS-W9 T were phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, one unidentified lipid and one unidentified aminolipid; minor amounts of another unidentified lipid and one unidentified aminophospholipid were also present (Fig.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…The fatty acid profile of strain BS-W9 T was distinguished from that of the type strain of H. namhaensis by differences in the presence and proportions of some fatty acids, particularly cyclo C 19 : 0 ω8 c and 11-methyl C 18 : 1 ω7 c (). The fatty acid profile of strain BS-W9 T could also be distinguished from those of some phylogenetically related taxa, Pseudopelagicola gijangensis , Pelagicola litoralis and Ascidiaceihabitans donghaensis , particularly by the presence of cyclo C 19 : 0 ω8 c (; Kim et al , 2014a, b, c). The major polar lipids detected in strain BS-W9 T were phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, one unidentified lipid and one unidentified aminolipid; minor amounts of another unidentified lipid and one unidentified aminophospholipid were also present (Fig.…”
mentioning
confidence: 94%
“…Comparative 16S rRNA gene sequence analysis showed that this novel strain is phylogenetically most closely related to the genus Halocynthiibacter of the family Rhodobacteraceae . The genus Halocynthiibacter was proposed by Kim et al (2014a) with the description of a single species with a validly published name, Halocynthiibacter namhaensis , which was isolated from a sea squirt collected from the South Sea, South Korea. The aim of the present work was to determine the exact taxonomic position of strain BS-W9 T by using a polyphasic characterization, which included determination of chemotaxonomic and other phenotypic properties, and detailed phylogenetic investigations based on 16S rRNA gene sequences and DNA–DNA hybridization.…”
mentioning
confidence: 97%
See 3 more Smart Citations